Composite material
Patent Information
- Application Number
- CN202580017845.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-04
- Filing Date
- 2025-03-03
- Publication Date
- 2026-09-25
AI Technical Summary
另一方面,与孔径较大的膜相比,这些较小的孔径通常会导致较低的流速和减少的通量
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
[0001] Cross-references to related applications This application claims the benefit of U.S. Provisional Application No. 63 / 560,832, filed March 4, 2024, the entire disclosure of which is incorporated herein by reference for all purposes. Technical Field
[0002] This specification relates generally to composite materials, and more specifically to composite materials configured as filter media. Background Technology
[0003] Nonwoven fibers are used in a wide variety of applications, such as filter media, insulation materials, medical applications (e.g., face masks and surgical gowns), battery separators, hygiene applications, clothing, food packaging, cosmetics, and many others. One specific application of nonwoven fibers is liquid filtration. Liquid filtration is the process of removing solid particles, impurities, and contaminants suspended in a fluid flow. It typically involves passing a process liquid (in the form of a slurry or suspension) through a permeable filter media, which then traps and retains the captured solids.
[0004] There are two main types of liquid filtration: surface filtration and depth filtration. Filtration methods are primarily distinguished by the structure of their filter media. Depth filtration is used to retain particles throughout the entire depth of the filter media. Depth filters typically use thick, multi-layered filter media with increasing density along the flow direction. Larger particles are retained at the filter surface, where the media density is lowest, while the particle size gradually decreases in the depth direction of the filter. The high pore volume of the filter provides a tortuous and difficult flow path for solids. The significant resistance it provides effectively prevents solid particles from being mixed into the filtrate.
[0005] Depth filters are typically used when the liquid being processed contains a wide range of particle sizes. Depth filters can filter particles smaller than the average pore size and have a high particle holding capacity, capturing large amounts of solids before clogging occurs. They can remove gel-like particles from process liquids. Finally, they have a long service life and require less frequent replacement, but are generally disposable products.
[0006] When determining the desired flow rate, key considerations are pore size and the required liquid flux. The membrane pore size is selected based on the expected performance of the final device. The pore size determines the membrane's functional properties, including flow rate and flux. For example, using a membrane with a smaller pore size generally improves the filter's efficiency in capturing contaminants. On the other hand, these smaller pore sizes typically result in lower flow rates and reduced flux compared to membranes with larger pore sizes. Summary of the Invention
[0007] This article provides a composite material and a method for manufacturing the composite material. This composite material can be configured for a variety of applications, including but not limited to liquid filters.
[0008] In one aspect, the composite material used as a filter medium comprises layers, sheets, or webs containing wet-laid fibers and meltblown fibers. The ratio of the maximum pore size to the average flow pore size (i.e., pore size distribution) of this layer is about 2.5 or less. A substantially uniform pore size distribution improves certain performance characteristics of the filter medium, such as service life, efficiency, and capacity, without significantly affecting the permeability and / or flow rate through the material.
[0009] In various embodiments, the maximum pore size of the composite material is about 30 micrometers or less. In some embodiments, the maximum pore size is about 20 micrometers or less, or about 13 micrometers or less.
[0010] In various embodiments, the average flow pore size of the composite material is about 15 micrometers or less. In some embodiments, the average flow pore size is about 10 micrometers or less, or about 7 micrometers or less.
[0011] In various implementations, the aperture distribution (i.e., the ratio of the maximum aperture to the average flow aperture) is about 2.0 or less, or about 1.5 or less.
[0012] In various embodiments, the basis weight of the wet-laid fibers is about 20 gsm to about 300 gsm, or about 50 gsm to about 200 gsm, or about 100 gsm to about 200 gsm. In one embodiment, the basis weight of the wet-laid fibers is at least about 100 gsm. In another embodiment, the basis weight of the wet-laid fibers is at least about 200 gsm.
[0013] In various embodiments, the basis weight of the meltblown fiber is about 20 gsm to about 300 gsm, or about 20 gsm to about 200 gsm, or about 20 gsm to about 100 gsm. In exemplary embodiments, the basis weight of the meltblown fiber is about 20 gsm, or about 40 gsm, or about 100 gsm.
[0014] Wet-laid fibers and meltblown fibers can be woven, interlaced, layered, fused, entangled, ultrasonically bonded, or bonded together in other ways known to those skilled in the art. In an exemplary embodiment, the layers are bonded together by ultrasonic bonding.
[0015] In various embodiments, the dust holding capacity of the composite material is at least about 24 mg / in. 2 In some implementations, the dust holding capacity is greater than about 60 mg / in. 2 or greater than approximately 100 mg / in 2.
[0016] In various embodiments, the composite material has improved efficiency in capturing contaminants, particularly contaminants contained in liquids. In exemplary embodiments, the composite material has an efficiency of at least 95% or higher in capturing particles with a maximum size of 17 micrometers or larger, or about 15 micrometers or larger, or about 10 micrometers or larger. In various embodiments, the material has an efficiency of at least about 95.4%, or at least about 96.7%, or at least about 98.3% in capturing particles with a size of about 25 micrometers.
[0017] Materials suitable for wet-laid fibers include, but are not limited to, polypropylene, polyester (PET), PEN polyester, PCT polyester, polypropylene, PBT polyester, copolyamide, polyethylene, high-density polyethylene (“HDPE”), LLDPE, cross-linked polyethylene, polycarbonate, polyacrylate, polyacrylonitrile, polyfuran, polystyrene, styrene-maleic anhydride, polymethylpentene, cyclic olefin copolymers or fluorinated polymers, polytetrafluoroethylene, perfluoroethylene and hexafluoropropylene or copolymers with PVDF such as P(VDF-TrFE) or terpolymers such as P(VDF-TrFE-CFE). ), propylene, polyimide, polyetherketone, cellulose ester, nylon and polyamide, polymethacrylic acid, poly(methyl methacrylate), polyoxymethylene, polysulfonate, acrylic acid, modified acrylic acid, styrene acrylic acid, pre-oxidized acrylic acid, fluorinated acrylic acid, vinyl acetate, vinyl acrylic acid, ethylene-vinyl acetate, styrene-butadiene, ethylene / vinyl chloride, vinyl acetate copolymer, latex, polyester copolymer, carboxylated styrene acrylic acid or vinyl acetate, epoxy resin, acrylic multi-component copolymer, phenolic resin, polyurethane, cellulose, styrene or any combination thereof.
[0018] In an exemplary embodiment, the wet-laid fibers are synthetic fibers, and at least some of the fibers in the second layer comprise polyester. In some embodiments, the wet-laid fibers are 100% polyester.
[0019] In various embodiments, meltblown fibers include, but are not limited to, any polymer having thermoplastic behavior, such as polypropylene, polystyrene, polyester, polyurethane, polyamide (nylon), polyethylene, polycarbonate, and combinations thereof. In an exemplary embodiment, the meltblown fiber comprises polyester.
[0020] In various embodiments, wet-laid fibers are produced by dispersing fibers in a liquid (such as water or foam) and depositing them onto a wire mesh, drying felt, or filter, to which the liquid is drained or removed to form a dried or thermally bonded web. In some embodiments, wet-laid fibers comprise foamed web fibers formed from a dispersion of such fibers in a foaming liquid.
[0021] In various implementations, meltblown fibers are produced by melting a polymer, extruding the polymer through an orifice or nozzle, and then blowing it into microfibers using high-temperature, high-speed air. The microfibers are collected on a rotating drum or forming belt with a vacuum below the surface to form a nonwoven web.
[0022] The fibers may have a thickness suitable for the application. In some embodiments, at least one dimension of the fiber is in the range of about 1 to about 10,000 micrometers, or about 1 to about 1,000 micrometers, or about 10 to 100 micrometers. The thickness of the fiber may also be measured in denier, a unit of measurement for fiber linear density. In some embodiments, the linear density of the fiber may be about 1 denier to about 15 deniers, or at least about 8 deniers, or at least about 10 deniers, or at least about 13 deniers.
[0023] In some embodiments, the composite material may also include a support structure, which may include a mesh support structure, such as a mesh, felt, grid, net, etc. In these embodiments, wet-laid fibers and meltblown fibers can be ultrasonically bonded to the strands of the mesh support structure (e.g., the mesh) at multiple attachment points. Ultrasonic bonding of fibers to the mesh is more convenient and less costly than using adhesives or other methods of laminating fibers to the mesh.
[0024] On the other hand, a product is provided that comprises the composite material described above. This product may include, for example, a filter medium for a liquid filter, or a liquid filter such as an oil filter, gas filter, fuel filter, hydraulic filter, chemical filter, etc.
[0025] On the other hand, the filter medium includes a first layer comprising wet-laid fibers and meltblown fibers, and a support structure in contact with the first layer.
[0026] In various embodiments, the maximum pore size of the filter medium is about 30 micrometers or less. In some embodiments, the maximum pore size is about 20 micrometers or less, or about 13 micrometers or less.
[0027] In various embodiments, the average flow pore size of the filter medium is about 15 micrometers or less. In some embodiments, the average flow pore size is about 10 micrometers or less, or about 7 micrometers or less.
[0028] In various embodiments, the filter medium has a reduced pore size distribution, i.e., the ratio of the maximum pore size to the average flow pore size is about 2.5 or less, or about 2 or less. In some embodiments, this ratio is less than 1.5.
[0029] In various implementations, the support structure is a mesh support structure, such as a mesh, felt, grid, or wire mesh. In these implementations, wet-laid fibers and meltblown fibers can be ultrasonically bonded to the strands of the mesh support structure (e.g., a mesh) at multiple attachment points.
[0030] In various embodiments, the basis weight of the mesh strands is at least about 80 gsm, or at least about 100 gsm, or at least about 110 gsm. In some embodiments, the average thickness of the mesh strands is at least about 0.20 inches or at least about 0.025 inches. This configuration increases the surface area of the strands, thereby providing stronger ultrasonic adhesion between the mesh and the fibers in the first layer.
[0031] Suitable materials for the mesh include, but are not limited to, high-density polyethylene (HDPE), polyethylene, polypropylene (PP), metallocene PP, polylactic acid (PLA), thermoplastic polymers, nylon, polybutylene terephthalate (PBT), thermoplastic elastomers (TBE), polyphenylene sulfide (PPS), polyvinylidene fluoride (PVDF), and combinations thereof. In an exemplary embodiment, the mesh comprises HDPE, PP, or a combination thereof. Attached Figure Description
[0032] The accompanying drawings are incorporated in and form part of this specification, illustrating several embodiments of the present disclosure and, together with the description, explaining the principles of the present disclosure.
[0033] Figure 1 A composite material comprising wet-laid fibers and meltblown fibers is shown; Figure 2 It is a cross-sectional view of a composite material comprising a first layer of meltblown fibers and wet-laid fibers, as well as a mesh layer; Figure 3 yes Figure 2 An exploded view of the mesh; Figure 4 A liquid filter cartridge is shown; Figure 5 A liquid bag filter is shown; Figure 6 A pleated filter element is shown; and Figure 7 A membrane filter cartridge is shown. Detailed Implementation
[0034] This specification and accompanying drawings illustrate exemplary embodiments and should not be considered limiting. The claims (including equivalents) define the scope of this disclosure. Various mechanical, compositional, structural, and operational changes may be made without departing from the scope of this specification and the claims (including equivalents). In some cases, well-known structures and techniques have not been shown or described in detail so as not to obscure this disclosure. Identical numbers in two or more drawings represent the same or similar elements. Furthermore, an element and its related aspects described in detail with reference to one embodiment may, where practically feasible, be included in other embodiments where that element and its related aspects are not specifically shown or described. For example, if an element is described in detail with reference to one embodiment but not with reference to a second embodiment, that element may still be claimed to be included in the second embodiment. Furthermore, the illustrations herein are for illustrative purposes only and do not necessarily reflect the actual shape, size, or dimensions of the system or the components shown.
[0035] It should be noted that, as used in this specification and the appended claims, the singular forms “a,” “an,” and “the,” and any singular use of any word, include plural references unless explicitly and unambiguously defined as a single reference. As used herein, the term “comprising” and its grammatical variations are intended to be non-restrictive, such that the description of items in the list does not exclude the possibility of replacing or adding other similar items to the listed items.
[0036] Composite materials are provided, configured for a variety of applications, such as filter media for liquid filters. These filter media can be used in a wide range of industries, including pulp and paper, food and beverage, steel production, industrial process fluids, municipal, automotive, power generation, semiconductor manufacturing, mining / construction, oil / chemical refining, medical / pharmaceutical, and general manufacturing.
[0037] For example, various implementation schemes include fuel filters, such as diesel fuel filters, hydrocarbon fuel filters, gasoline fuel filters, canister fuel filters, pipeline fuel filters, in-tank fuel filters, cartridge fuel filters, carburetor inlet filters, pump outlet fuel filters, spin-on fuel filters, etc.
[0038] For example, various implementation schemes include gas turbine and compressor inlet filters, plate filters, filter presses, drum filters, water treatment plant filters, biological filters, membrane bioreactor membranes, hydrocarbon filters, diesel filters, fuel filters, hydraulic fluid filters, food and beverage filters, semiconductor filters, microfiltration membranes, downstream membrane filtration, pharmaceutical and medical filters, wastewater filters, industrial process and / or municipal filters, pipeline gas turbine and compressor inlet filters, plate filters, cartridge filters, bag filters, clean-in-situ (CIP) filters, battery separators, etc.
[0039] For example, various implementations include semiconductor processing filters for filtering nanoscale particles and harmful contaminants during logic circuit and chip manufacturing processes, including microfiltration filters with hydrophobic or hydrophilic membranes, chemical filters, CMP filters, lithography filters, process gas filters and purifiers, chemical mechanical polishing filters, electroplating solution filters, wastewater filters, wet etching and cleaning filters, PFOA filters, etc.
[0040] For example, various implementations include filters for the food and beverage industry to remove solid and / or liquid contaminants, such as filters for making juices and soft drinks, water filters in sinks and kettles, basket centrifuges for salt production, disc centrifuges for separating cream from milk, water purification membranes, rotary vacuum drum filters for separating syrup from sludge, hydrocyclones for purifying starch, disc or tubular centrifuges for refining vegetable seed oils, and settling centrifuges or filter presses for dehydrating separated grains in, for example, breweries or breweries.
[0041] For example, various implementations include filters for the pharmaceutical industry, for plasma separation, special enzymes, vitamins, diagnostics, herbal medicines, red biotechnology, white biotechnology, and may include filters such as magnetic filters, bag filters, self-cleaning filters, reverse osmosis membranes, ultrafiltration membranes, and nanofiltration membranes.
[0042] For example, in various embodiments, industrial filters are provided for removing solid and / or liquid contaminants from liquid process streams in refining, petrochemical, chemical, oil and gas, paint manufacturing, organic solvents, inks, oil and kerosene industrial water treatment, cosmetics, wineries, and pharmaceuticals. These filters include pleated filter cartridges, melt-blown filter cartridges, wound-wire filter cartridges, membrane filter cartridges, activated carbon filter cartridges, wound fiber deep liquid filter cartridges, stainless steel filter cartridges, pleated series liquid filter cartridges, and other specialty filter cartridges. The precision of these filters ranges from less than about 1 micrometer to about 100 micrometers.
[0043] For example, hydraulic filters are provided for removing particulate matter from hydraulic fluids. Hydraulic filters can be full-flow or split-flow types, and may include, but are not limited to, oil filters, spin-on filters, return line filters, dual filters, offline and online filters, and tank filters.
[0044] For example, various implementation schemes include municipal filters, such as those used in water treatment plants. These filters may include, but are not limited to, screen filters, slow sand filters, disc filters, fast sand filters, membrane filters, bag filters, reverse osmosis filters, etc.
[0045] For example, various implementation schemes include gas pipeline filters, such as turbine air filters, particulate filters, clay treatment filters, amine filters, two-stage coalescing separators, coarse filters, natural gas pipeline filters, Y-type filters, T-type filters, basket filters, magnetic filters, backwash filters, etc.
[0046] For example, various implementation schemes include power generation filters, such as hydroelectric power generation filters, solar power generation filters, nuclear power generation filters, water filter cartridges, sintered metal filters, wedge wire mesh filters, demister pad filters, etc.
[0047] For example, various embodiments include a battery separator that acts as a mechanical barrier between electrodes to prevent short circuits while allowing ions to pass through the electrolyte in the pores. For example, various embodiments include alkaline battery separators, including but not limited to zinc-manganese dioxide (Zn / MnO2), nickel-cadmium (Ni-Cd), and nickel-hydrogen (Ni-H2) batteries. The battery separator may include a substrate comprising a blend of polyvinyl alcohol (PVA) fibers with cellulose or cellulose derivatives (such as rayon or lyocell).
[0048] While the following description focuses primarily on filter media and liquid filters, the apparatus and methods disclosed herein are readily adaptable to a wide range of other applications. For example, the filter media disclosed herein can be used in household cleaning products, roofing and flooring products, automotive interiors and headliners, reusable bags, wall coverings, filtration devices, insulation materials, and more. Furthermore, the individual nanoparticles separated and generated in the methods described herein can be used in a variety of coatings, composites, and / or additives, such as polymers, food packaging, flame retardants, fuel cells, batteries, capacitors, nanoceramics, lighting equipment, materials manufacturing, manufacturing methods, composite reinforcement, cement and other materials, medical diagnostic applications, medical treatment devices or therapies, tissue engineering (e.g., bone or tissue repair scaffolds), drinking water, industrial process fluids, food and beverage products, pharmaceuticals and biologics, tissue imaging, medical therapy delivery, environmental applications (e.g., biodegradable compounds), and more.
[0049] Now for reference Figure 1 The composite material 100 comprises layers of wet-laid fibers 110 and meltblown fibers 120. The wet-laid fibers 110 and meltblown fibers 120 may be woven, interlaced, laminated, fused, entangled, ultrasonically bonded, or bonded together in other ways known to those skilled in the art. The fibers 110 and 120 may form layer, sheet, or web structures bonded together by mechanical, thermal, or chemical entanglement of fibers or filaments. In an exemplary embodiment, the fibers 110 and 120 are bonded together by ultrasonic bonding.
[0050] Wet-laid fibers, as defined herein, are fibers produced by dispersing the fibers in a liquid (such as water or foam) and depositing them onto a frame or forming mesh, drying felt, or filter, to which the liquid is drained or removed to form a dried or thermally bonded web. Wet-laid methods typically involve providing short or discrete fibers with lengths from about 2 mm to about 15 mm, preferably from about 4 mm to about 8 mm. In some embodiments, the fibers may be mixed with viscose pulp or wood pulp.
[0051] In an exemplary embodiment, wet-laid fiber 110 is foam-laid fiber. Foam-laid fiber, as defined herein, is a fiber formed from a dispersion of fibers in a foaming liquid. First, pulp or fiber furnish is prepared in a pulper, then dewatered and mixed with a foam or foamable liquid containing a surfactant and water. The fibers are dispersed in the foam, and the resulting fiber-foam is deposited onto a wire mesh. The bulk of the liquid (primarily in foam form) is removed by suction. The surfactant can be of any suitable type, such as anionic, cationic, nonionic, and amphoteric surfactants. Additionally, wet strength agents, binders, wrinkling chemicals, etc., can be used. Surfactants used in the foaming process are generally considered to have a negative impact on both the dry and wet tensile strength of the paper web.
[0052] The foam forming process uses water as a binding element, but leverages the bubble structure and rheological properties of the wet foam to keep the fibers separated. Therefore, the foam flow during forming can be laminar, thereby controlling the fiber distribution and orientation. Furthermore, foam stability affects the density of the final material, and the average pore size can be customized by adjusting the bubble size.
[0053] Meltblown fibers 120 are produced by melting a polymer, extruding the polymer through an orifice or nozzle, and then blowing it into microfibers using high-temperature, high-speed air. The microfibers are collected on a drum or forming belt with a vacuum below the surface to form a nonwoven web. Suitable meltblown fibers include any polymer with thermoplastic behavior, such as polypropylene, polystyrene, polyester, polyurethane, polyamide (nylon), polyethylene, polycarbonate, and combinations thereof.
[0054] The basis weight of the fibers is selected to optimize adhesion and increase the overall strength of material 100. In embodiments where material 100 is used as a filter medium, the filter has a longer service life, efficiency, and capacity without affecting other performance factors such as air permeability and flux.
[0055] In various embodiments, the basis weight of the wet-laid fibers is about 20 gsm to about 300 gsm, or about 50 gsm to about 200 gsm, or about 100 gsm to about 200 gsm. In one embodiment, the basis weight of the wet-laid fibers is at least about 100 gsm. In another embodiment, the basis weight of the wet-laid fibers is at least about 200 gsm.
[0056] In various embodiments, the basis weight of the meltblown fiber is about 20 gsm to about 300 gsm, or about 20 gsm to about 200 gsm, or about 20 gsm to about 100 gsm. In exemplary embodiments, the basis weight of the meltblown fiber is about 20 gsm, or about 40 gsm, or about 100 gsm.
[0057] The fibers may have a thickness suitable for the application. In some embodiments, at least one dimension of the fiber is in the range of about 1 to about 10,000 micrometers, or about 1 to about 1,000 micrometers, or about 10 to 100 micrometers. The thickness of the fiber may also be measured in denier, a unit of measurement for fiber linear density. For gas filters, such as pleated or non-pleated air filters, the linear density of the fiber may be about 1 denier to about 10 deniers. The composite material may contain fibers having the same or different linear deniers. In some embodiments, the linear density of the wet-laid fiber may be about 1 denier to about 15 deniers, or at least about 8 deniers, or at least about 10 deniers, or at least about 13 deniers.
[0058] The composite material 100 may have a thickness suitable for a particular application. In some embodiments, the thickness of the composite material 100 is from about 0.0508 mm to about 1.016 mm, preferably from about 0.127 mm to about 0.635 mm.
[0059] The cross-section of the fiber can have various shapes, including but not limited to circular, kidney-shaped, dog-bone-shaped, trefoil-shaped, dumbbell-shaped, butterfly-shaped, star-shaped, and Y-shaped. Each segment contains a different range of denier fibers. The fiber may include a bio-component fiber comprising two or more different fibers bonded together. The fiber may contain the same or different materials. The fiber may contain a bio-component fiber having a core and a sheath. The longitudinal axis of the core relative to the sheath may be concentric or eccentric.
[0060] Fibers 110 and 120 can be man-made or natural. Suitable materials for the fibers include, but are not limited to, polypropylene, polyester (PET), PEN polyester, PCT polyester, polypropylene, PBT polyester, copolyamide, polyethylene, high-density polyethylene (“HDPE”), LLDPE, cross-linked polyethylene, polycarbonate, polyacrylate, polyacrylonitrile, polyfuranolol, polystyrene, styrene-maleic anhydride, polymethylpentene, cyclic olefin copolymers or fluorinated polymers, polytetrafluoroethylene, perfluoroethylene and hexafluoropropylene or copolymers with PVDF such as P(VDF-TrFE) or terpolymers such as P(VDF-TrFE-CFE). Acrylic, polyimide, polyetherketone, cellulose esters, nylon and polyamide, polymethacrylic acid, poly(methyl methacrylate), polyoxymethylene, polysulfonates, acrylics, modified acrylics, styrene-modified acrylics, pre-oxidized acrylics, fluorinated acrylics, vinyl acetate, vinyl acrylics, ethylene-vinyl acetate, styrene-butadiene, ethylene / vinyl chloride, vinyl acetate copolymers, latex, polyester copolymers, carboxylated styrene acrylics or vinyl acetate, epoxy resins, acrylic multi-component copolymers, phenolic resins, polyurethane, cellulose, styrene, or any combination thereof. Other conventional fiber materials may also be considered.
[0061] In an exemplary embodiment, at least some of the wet-laid fibers 110 comprise polyester. In some embodiments, the fibers are 100% polyester.
[0062] In an exemplary embodiment, at least some of the meltblown fibers 120 comprise polyester.
[0063] In some embodiments, the fibers may include thermally split bicomponent fibers to reduce the fiber size of at least some components of the fibers within the filter media. This reduced fiber size increases the specific surface area, thereby improving the overall efficiency of such filters in capturing contaminants, particularly those ranging in size from about 0.1 to about 1 micrometer (i.e., E1 particles), without affecting other important filter characteristics such as pressure drop and permeability. The bicomponent fibers may include any suitable shape, such as core / sheath structures with concentric cores, core / sheath structures with eccentric cores, side-by-side structures with solid or hollow cores, side-by-side structures with concentric or eccentric hollow cores, fan-shaped segmented structures with solid or hollow cores, striped fibers, conductive fibers, island-type structures, hybrid fibers, or combinations thereof.
[0064] The fiber can be a short fiber or a continuous fiber. The fiber can be bare (e.g., without spinning oil) or may contain spinning oil. Spinning oil may include, but is not limited to, lubricants, emulsifiers, antistatic agents, antimicrobial agents, binders, and wetting agents. Other organic liquids, such as alcohols or blends of organic liquids, may be added to the spinning oil. The spinning oil may be applied, for example, during fiber carding, during melt spinning operations, or during fiber stretching, crimping, and cutting operations.
[0065] In various embodiments, the maximum pore size of the composite material is about 30 micrometers or less. In some embodiments, the maximum pore size is about 20 micrometers or less, or about 13 micrometers or less.
[0066] In various embodiments, the average flow pore size of the composite material is about 15 micrometers or less. In some embodiments, the average flow pore size is about 10 micrometers or less, or about 7 micrometers or less.
[0067] In various embodiments, the composite material has a reduced pore size distribution, i.e., the ratio of the maximum pore size to the average flow pore size is about 2.5 or less, or about 2 or less. In some embodiments, this ratio is less than 1.5.
[0068] In an exemplary embodiment, the porosity value of the composite material is from about 85% to about 97%, or from about 90% to about 95%. The porosity value is defined as the fraction of the non-solid or pore volume in the total volume of the material.
[0069] In various implementation schemes, the dust holding capacity of the composite material is at least about 24 mg / in. 2 In some implementations, the dust holding capacity is greater than about 60 mg / in. 2 or greater than approximately 100 mg / in 2 .
[0070] In various embodiments, the composite material has improved efficiency in capturing contaminants. In exemplary embodiments, the composite material captures particles with a maximum size of 17 micrometers or larger, or about 15 micrometers or larger, or about 10 micrometers or larger with an efficiency of 95% or higher. In various embodiments, the material captures particles with a maximum size of about 25 micrometers with an efficiency of at least about 95.4%, or at least about 96.7%, or at least about 98.3%.
[0071] In some embodiments, the composite material 140 may further include one or more support structures (not shown), which may include a mesh support structure 160, such as a mesh, felt, grid, wire mesh, etc. In these embodiments ( Figure 2 and Figure 3As shown, wet-laid fibers and meltblown fibers (shown as a layer 150) can be ultrasonically bonded to the strands of a mesh support structure 160 (e.g., a mesh) at multiple attachment points. Ultrasonic bonding of fibers to the mesh 160 is more convenient and less costly than using adhesives or other methods of laminating fibers onto a mesh.
[0072] For example, wet-laid and meltblown fibers 150 and mesh 160 can be fed into an ultrasonic bonding apparatus that applies high-frequency ultrasonic vibrations to melt the strands of the mesh at multiple attachment points and / or bond the strands of the mesh to the fibers 150. To achieve this bonding, the fibers 150 and mesh 160 are conveyed through the gap between the ultrasonic vibrating unit (e.g., a welding head) and the matching tool (e.g., an anvil or drum) of the ultrasonic apparatus. The ultrasonic apparatus applies little or no pressure to the fibers or mesh. This allows the thickness or bulk of the fibers to be substantially maintained when bonding them to the mesh.
[0073] Suitable materials for the mesh include, but are not limited to, high-density polyethylene (HDPE), low-density polyethylene, polyethylene, polypropylene (PP), metallocene PP, polylactic acid (PLA), thermoplastic polymers, nylon, polybutylene terephthalate (PBT), thermoplastic elastomer (TBE), polyphenylene sulfide (PPS), polyvinylidene fluoride (PVDF), and combinations thereof. In an exemplary embodiment, the mesh comprises HDPE, PP, and combinations thereof.
[0074] The mesh can be formed by any suitable method, such as extrusion, co-extrusion, bicomponent, and elastomeric meshes. In an exemplary embodiment, the mesh is formed by a single extrusion method. Typically, a suitable method for manufacturing an extruded mesh involves extruding a polymer blend composition through a die having reciprocating or rotating components to form a mesh configuration. This forms cross-machine direction strands that intersect with continuously flowing machine direction strands. After extrusion, the mesh is typically stretched in the machine direction using the differential speed between two sets of pressure rollers.
[0075] like Figure 3 As shown, the aperture 150 can be formed by a first set of strands 152 extending in one direction and a second set of strands 154 extending in a generally intersecting or transverse direction. The first set of strands 152 and the second set of strands 154 are extruded polymer elongated members that intersect and cross during extrusion to form a mesh-like structure. The strands can also be formed by weaving extruded strands together, rather than crossing them during extrusion. In some embodiments, the strands are made of the same material. In other embodiments, the first set of strands 152 is made of a different material than the second set of strands 154.
[0076] The strands can be formed at an angle of about 10 to about 90 degrees, or about 50 to about 80 degrees, or about 60 degrees. In exemplary embodiments, the holes formed by the strands are symmetrical, but it should be appreciated that in some embodiments, the holes can be asymmetrical. The strand density is preferably less than about 100 strands / inch, or less than about 50 strands / inch, or less than about 44 strands / inch.
[0077] The basis weight of strands 152 and 154 is preferably at least about 80 gsm, or at least about 100 gsm, or at least about 110 gsm. The average thickness 158 of strands 152 and 154 is preferably from about 0.006 inches to about 0.0400 inches, or from about 0.02 inches to about 0.03 inches, or from about 0.025 inches to about 0.026 inches. In an exemplary embodiment, the average thickness of the strands is about 0.0254 inches.
[0078] Figure 4 A representative liquid filter 201 produced using the composite materials described herein in various embodiments is illustrated. The composite materials are rolled into cylinders, cones, or other suitable shapes and can be used in applications such as gas turbine and compressor inlet filters, plate filters, etc. The filter element is a tubular filter medium encapsulated within a housing. The flow direction in a cartridge filter is typically from the outside to the inside of the filter element. Filter elements are typically made of synthetic or natural fibers and small metal wires. A core made of stainless steel, tin-plated steel, or polypropylene is located on the axis of the tubular filter element to support the media material. A purer filtrate is collected at the core.
[0079] Figure 5 A representative bag filter 202 manufactured using composite materials from various embodiments described herein is illustrated. Bag filters are among the most popular filtration devices. In this device, process liquid flows through a permeable bag with micropores that acts as the filter medium. Solid particles larger than the pores are trapped and accumulate inside the bag. A sealing ring, typically made of stainless steel or plastic, is located at one end to secure the bag inside the filter container.
[0080] Figure 6 A representative pleated filter element 212 is illustrated, produced using composite materials from various embodiments described herein. Filter element 112 is particularly suitable for surface filtration and can be constructed by pleating the media bonded to its ends to provide a larger filtration area in a minimal volume.
[0081] Figure 7An example is illustrated of a membrane filter element 218 manufactured using composite materials from various embodiments described herein. Filter element 118 is particularly suitable for the food and beverage, pharmaceutical, UPW, and semiconductor industries. Filter element 118 may comprise PTFE, PES, PVDF, and / or nylon and may have a pleated filtration structure. The pleated structure provides each pleated membrane filter element with a large filtration area and high dust holding capacity, thus effectively extending its service life.
[0082] Other types of liquid filters that can be developed using the materials disclosed herein include conical filter cartridges, spunbond filter cartridges, square end cap filter cartridges, activated carbon filter cartridges, reverse osmosis membrane filter cartridges, alkaline filter cartridges, battery separators, ultraviolet filter cartridges, bag filters, V-type compact filters, plate filters, flat panel unit filters, pleated or non-pleated bag filter cartridges, in-situ cleaning (CIP) filters, etc.
[0083] Example The applicant manufactured and tested several different composite materials used as filter media, comprising 100% polyester wet-laid fibers and meltblown fibers. The wet-laid fibers had a basis weight of approximately 100 gsm. The samples also included: (1) meltblown fibers with a basis weight of 20 gsm and containing polyester (sample 1); (2) meltblown fibers with a basis weight of 40 gsm and containing polyester (sample 2); (3) meltblown fibers with a basis weight of 40 gsm and containing polyester (sample 3); (4) meltblown fibers with a basis weight of 100 gsm and containing polyester (sample 4); (5) meltblown fibers with a basis weight of 40 gsm and containing polyester (sample 5); and (6) meltblown fibers with a basis weight of 100 gsm and containing polyester (sample 6).
[0084] The applicant tested the dust holding capacity of the aforementioned composite material (in grams and mg / in). 2 (in micrometers), pollutant capture efficiency (number of micrometers for 95% efficiency and percentage efficiency for 25 micrometers), average and maximum flow rate, orifice size (in micrometers), bubble point (in inH2O), and permeability (in cfm / ft). 2 The test results are measured in units of per minute (%) and porosity (%). Dust holding capacity was tested according to J905 standard, and efficiency was tested according to J1985 standard. Porosity is defined as the fraction of non-solid or pore volume in the total volume of the material. The test results are shown in Tables 1 and 2 below.
[0085] Table 1 Table 2 The last two samples (samples 5 and 6) underwent calendering. The first four samples were not calendered. It should be noted that the calendering step significantly reduced the maximum pore size and the average flow pore size. For example, sample 5 has an average flow pore size of approximately 6.6 μm and a maximum pore size of approximately 12.8 μm. Sample 6 has an average flow pore size of approximately 4.77 μm and a maximum pore size of approximately 11.48 μm. The pore size distribution (PSD), or the ratio of maximum pore size to average flow pore size, is less than 2 for sample 5, and less than 2.5 for sample 6. For samples 1-4, the PSD is less than 2 for all samples. Reducing the PSD results in a more uniform structure and controlled porosity, thereby improving the material's efficiency in trapping particles.
[0086] It should also be noted that all samples captured contaminants with an efficiency of at least 95% of the contaminants corresponding to micrometers less than 17. Therefore, all samples captured at least 95% of contaminants 17 micrometers or larger. Furthermore, all samples captured over 95% of contaminants 25 micrometers. Calendered samples 5 and 6 were particularly effective; sample 5 captured at least 95% of contaminants 11 micrometers or larger, and sample 6 captured at least 95% of contaminants 10 micrometers or larger. The porosity of samples 1-6 is greater than 91%, or at least approximately 91.79%.
[0087] The applicant also manufactured and tested a variety of different composite materials used as filter media, comprising 100% polyester wet-laid fibers and meltblown fibers. The wet-laid fibers had a basis weight of approximately 200 gsm. The samples also included: (1) meltblown fibers with a basis weight of 20 gsm and containing polyester (sample 7); (2) meltblown fibers with a basis weight of 40 gsm and containing polyester (sample 8); (3) meltblown fibers with a basis weight of 40 gsm and containing polyester (sample 9); (4) meltblown fibers with a basis weight of 100 gsm and containing polyester (sample 10); (5) meltblown fibers with a basis weight of 40 gsm and containing polyester (sample 11); and (6) meltblown fibers with a basis weight of 100 gsm and containing polyester (sample 12).
[0088] The applicant tested the dust holding capacity of the aforementioned composite material (in grams and mg / in). 2 (in micrometers), pollutant capture efficiency (number of micrometers for 95% efficiency and percentage efficiency for 25 micrometers), average and maximum flow rate, orifice size (in micrometers), bubble point (in inH2O), and permeability (in cfm / ft). 2 The dust holding capacity (per min) and porosity (%) were measured. Dust holding capacity was tested according to J905 standard, and efficiency was tested according to J1985 standard. Porosity was defined as the fraction of non-solid or pore volume in the total volume of the material. Test results are shown in Tables 3 and 4 below.
[0089] Table 3 Table 4 The last two samples (samples 11 and 12) underwent calendering. The first four samples (samples 7-10) were not calendered. It should be noted that the calendering step significantly reduced the maximum pore size and the average flow pore size. For example, sample 11 has an average flow pore size of approximately 7.13 μm and a maximum pore size of approximately 17.1 μm. Sample 12 has an average flow pore size of approximately 5.46 μm and a maximum pore size of approximately 12.12 μm. The pore size distribution (PSD), or the ratio of maximum pore size to average flow pore size, for samples 11 and 12 is less than 2.5. For samples 7-10, the PSD for all samples is less than 2. Reducing the PSD results in a more uniform structure and controlled porosity, thereby improving the material's efficiency in trapping particles.
[0090] It should also be noted that the number of micrometers corresponding to a contaminant capture efficiency of at least 95% for all samples was less than 17. Therefore, all samples captured at least 95% of contaminants of 17 micrometers or larger. Furthermore, all samples captured more than 95% of contaminants of 25 micrometers. Calendered samples 11 and 12 were particularly effective; sample 11 captured at least 95% of contaminants of 13 micrometers or larger, and sample 12 captured at least 95% of contaminants of 9 micrometers or larger. The porosity of samples 7-12 was greater than 90%, or at least approximately 90.9%.
[0091] Other embodiments will be apparent to those skilled in the art upon consideration of this specification and the practices of the embodiments disclosed herein. This specification and the examples are intended to be illustrative only, and the true scope and spirit of the embodiments are indicated by the appended claims.
[0092] For example, in a first aspect, a first embodiment is a composite material used as a filter medium. The composite material comprises layers of wet-laid fibers and melt-blown fibers. The ratio of the maximum pore size to the average flow pore size of the layer is about 2.5 or less.
[0093] The second implementation scheme is the first implementation scheme, wherein the maximum aperture is less than about 30 micrometers.
[0094] The third implementation scheme is any combination of the first two implementation schemes, wherein the average flow orifice diameter is less than about 15 micrometers.
[0095] The fourth embodiment is any combination of the first three embodiments, wherein the ratio of the maximum pore size of the material to the average flow pore size is about 2.0 or less.
[0096] The fifth embodiment is any combination of the first four embodiments, wherein the ratio of the maximum pore size of the material to the average flow pore size is about 1.5 or less.
[0097] The sixth embodiment is any combination of the first five embodiments, wherein the bubble point of the material is less than or equal to about 20 in / H2O.
[0098] The seventh embodiment is any combination of the first six embodiments, wherein the dust holding capacity of the material is at least about 24 mg / in. 2 .
[0099] The eighth embodiment is any combination of the first seven embodiments, wherein the material captures particles with a maximum size of about 25 micrometers with an efficiency of at least about 95.4%.
[0100] The ninth embodiment is any combination of the first eight embodiments, wherein the material captures particles with a maximum size of 17 micrometers or larger with an efficiency of 95% or higher.
[0101] The tenth embodiment is any combination of the first nine embodiments, wherein the material has an air permeability of approximately 66 cfm / ft. 2 / min or less.
[0102] The 11th embodiment is any combination of the first 10 embodiments, wherein the basis weight of the wet-laid web fibers is at least about 50 gsm.
[0103] The 12th implementation scheme is any combination of the first 11 implementation schemes, wherein the basis weight is from about 50 gsm to about 200 gsm.
[0104] The 13th implementation scheme is any combination of the first 12 implementation schemes, with a basis weight of approximately 100 gsm.
[0105] The 14th implementation scheme is any combination of the first 13 implementation schemes, wherein the wet web-forming fiber is a foam web-forming fiber.
[0106] The 15th embodiment is any combination of the first 14 embodiments, wherein the wet-laid fibers comprise materials selected from the group consisting of polypropylene, polyester, polypropylene, copolyamide, polyethylene, polycarbonate, polyacrylate, polyacrylonitrile, polystyrene, styrene-maleic anhydride, propylene, polyimide, polyetherketone, cellulose ester, nylon and polyamide, acrylics, vinyl acetate, ethylene-vinyl acetate, styrene-butadiene, ethylene / vinyl chloride, vinyl acetate copolymer, latex, epoxy resin, polyurethane, cellulose, styrene, and combinations thereof.
[0107] The 16th embodiment is any combination of the first 15 embodiments, wherein the wet-laid web fibers comprise polyester.
[0108] The 17th embodiment is any combination of the first 16 embodiments, wherein the meltblown fiber comprises a material selected from the group consisting of polyesters.
[0109] The 18th embodiment is any combination of the first 17 embodiments, and also includes a support structure in contact with at least one of the first and second layers.
[0110] Implementation scheme 19 is any combination of the first 18 implementation schemes, wherein the support structure includes a mesh containing strands.
[0111] Implementation scheme 20 is any combination of the first 19 implementation schemes, wherein the basis weight of the strand is at least about 100 gsm.
[0112] Implementation scheme 21 is any combination of the first 20 implementation schemes, wherein the basis weight is at least about 110 gsm.
[0113] The 22nd implementation scheme is any combination of the first 21 implementation schemes, wherein the support structure is ultrasonically bonded to the first and second layers at multiple attachment points.
[0114] The 23rd embodiment is any combination of the first 22 embodiments, wherein the mesh comprises materials selected from the group consisting of high-density polyethylene (HDPE), polyethylene, polypropylene (PP), metallocene PP, polylactic acid (PLA), thermoplastic polymers, nylon, polybutylene terephthalate (PBT), thermoplastic elastomer (TBE), polyphenylene sulfide (PPS), polyvinylidene fluoride (PVDF), and combinations thereof.
[0115] The 24th embodiment is any combination of the first 23 embodiments, wherein the porosity of the layer is about 90% to about 95%.
[0116] On the other hand, a filter medium is provided which comprises a composite material of any combination of the first 24 embodiments.
[0117] On the other hand, a liquid filtration medium is provided, comprising a composite material of any combination of the first 24 embodiments.
[0118] On the other hand, an oil filter is provided which comprises a composite material of any combination of the first 24 embodiments.
[0119] On the other hand, a gas filter is provided comprising a composite material of any combination of the first 24 embodiments.
[0120] On the other hand, a fuel filter is provided that comprises a composite material of any combination of the first 24 embodiments.
[0121] On the other hand, a hydraulic filter is provided that comprises a composite material in any combination of the first 24 embodiments.
[0122] On the other hand, a chemical filter is provided comprising a composite material of any combination of the first 24 embodiments.
[0123] On the other hand, a first embodiment is a fuel filter comprising a first layer containing wet-laid fibers and meltblown fibers, and a support structure in contact with the first layer.
[0124] The second implementation scheme is the first implementation scheme, wherein the maximum pore size of the filter medium is less than about 30 micrometers.
[0125] The third implementation scheme is any combination of the first two implementation schemes, wherein the average flow pore size of the filter medium is less than about 15 micrometers.
[0126] The fourth embodiment is any combination of the first three embodiments, wherein the ratio of the maximum pore size of the filter medium to the average flow pore size is about 2.5 or less.
[0127] The fifth embodiment is any combination of the first four embodiments, wherein the basis weight of the wet-laid web fibers is at least about 50 gsm.
[0128] The sixth implementation scheme is any combination of the first five implementation schemes, wherein the basis weight is from about 50 gsm to about 200 gsm.
[0129] The seventh implementation scheme is any combination of the first six implementation schemes, with a basis weight of approximately 100 gsm.
[0130] The eighth implementation scheme is any combination of the first seven implementation schemes, wherein the wet web-forming fiber is a foam web-forming fiber.
[0131] The ninth embodiment is any combination of the first eight embodiments, wherein the wet-laid fibers comprise materials selected from the group consisting of polypropylene, polyester, polypropylene, copolyamide, polyethylene, polycarbonate, polyacrylate, polyacrylonitrile, polystyrene, styrene-maleic anhydride, propylene, polyimide, polyetherketone, cellulose ester, nylon and polyamide, acrylics, vinyl acetate, ethylene-vinyl acetate, styrene-butadiene, ethylene / vinyl chloride, vinyl acetate copolymer, latex, epoxy resin, polyurethane, cellulose, styrene, and combinations thereof.
[0132] The 10th embodiment is any combination of the first 9 embodiments, wherein the wet-laid web fiber comprises polyester.
[0133] The 11th embodiment is any combination of the first 10 embodiments, wherein the meltblown fiber comprises polyester.
[0134] The 12th implementation scheme is any combination of the first 11 implementation schemes, wherein the support structure includes a mesh containing strands.
[0135] The 13th implementation scheme is any combination of the first 12 implementation schemes, wherein the basis weight of the strand is at least about 100 gsm.
[0136] The 14th implementation scheme is any combination of the first 13 implementation schemes, wherein the basis weight is at least about 110 gsm.
[0137] The 15th implementation scheme is any combination of the first 14 implementation schemes, wherein the support structure is ultrasonically bonded to the first layer at multiple attachment points.
[0138] The 16th embodiment is any combination of the first 15 embodiments, wherein the mesh comprises materials selected from the group consisting of high-density polyethylene (HDPE), polyethylene, polypropylene (PP), metallocene PP, polylactic acid (PLA), thermoplastic polymers, nylon, polybutylene terephthalate (PBT), thermoplastic elastomer (TBE), polyphenylene sulfide (PPS), polyvinylidene fluoride (PVDF), and combinations thereof.
[0139] The 17th embodiment is any combination of the first 16 embodiments, wherein the porosity of the first layer is about 90% to about 95%.
[0140] On the other hand, a liquid filter medium is provided, comprising any combination of the filter media of the first 17 embodiments.
Claims
1. A composite material for use as a filter medium, said composite material comprising: A layer comprising wet-laid fibers and meltblown fibers; and The ratio of the maximum pore size to the average flow pore size of the layer is about 2.5 or less.
2. The composite material according to claim 1, wherein the maximum pore size is less than about 30 micrometers.
3. The composite material according to claim 1, wherein the wet-laid fibers and the meltblown fibers are calendered, and the maximum pore size is less than about 13 micrometers.
4. The composite material according to claim 1, wherein the average flow pore size is less than about 15 micrometers.
5. The composite material according to claim 1, wherein the wet-laid fibers and the meltblown fibers are calendered, and the average flow pore size is less than about 7 micrometers.
6. The composite material according to claim 1, wherein the ratio is about 2.0 or less.
7. The composite material according to claim 1, wherein the ratio is about 1.5 or less.
8. The composite material according to claim 1, wherein the bubble point of the material is less than or equal to about 20 in / H2O.
9. The composite material according to claim 1, wherein the dust holding capacity of the material is at least about 24 mg / in 2 .
10. The composite material of claim 1, wherein the material has an efficiency of at least about 95.4% in capturing particles with a maximum size of about 25 micrometers.
11. The composite material of claim 1, wherein the material captures particles with a maximum size of 17 micrometers or larger with an efficiency of 95% or higher.
12. The composite material according to claim 1, wherein the air permeability of the material is about 66 cfm / ft. 2 / min or less.
13. The composite material according to claim 1, wherein the basis weight of the wet-laid fibers is at least about 50 gsm.
14. The composite material according to claim 13, wherein the basis weight is from about 50 gsm to about 200 gsm.
15. The composite material according to claim 1, wherein the basis weight of the meltblown fiber is from about 20 gsm to about 100 gsm.
16. The composite material according to claim 1, wherein the wet-laid fiber is a foam-laid fiber.
17. The composite material according to claim 1, wherein the wet-laid fibers comprise materials selected from the group consisting of polypropylene, polyester, polypropylene, copolyamide, polyethylene, polycarbonate, polyacrylate, polyacrylonitrile, polystyrene, styrene-maleic anhydride, propylene, polyimide, polyetherketone, cellulose ester, nylon and polyamide, acrylics, vinyl acetate, ethylene-vinyl acetate, styrene-butadiene, ethylene / vinyl chloride, vinyl acetate copolymer, latex, epoxy resin, polyurethane, cellulose, styrene, and combinations thereof.
18. The composite material according to claim 1, wherein the wet-laid fibers comprise polyester.
19. The composite material according to claim 1, wherein the meltblown fiber comprises polyester.
20. The composite material of claim 1, further comprising a support structure in contact with at least one of the first layer and the second layer.
21. The composite material of claim 20, wherein the support structure comprises a mesh containing strands.
22. The composite material of claim 21, wherein the basis weight of the strands is at least about 100 gsm.
23. The composite material according to claim 22, wherein the basis weight is at least about 110 gsm.
24. The composite material of claim 20, wherein the support structure is ultrasonically bonded to the first and second layers at a plurality of attachment points.
25. The composite material of claim 21, wherein the mesh comprises a material selected from the group consisting of high-density polyethylene (HDPE), polyethylene, polypropylene (PP), metallocene PP, polylactic acid (PLA), thermoplastic polymers, nylon, polybutylene terephthalate (PBT), thermoplastic elastomer (TBE), polyphenylene sulfide (PPS), polyvinylidene fluoride (PVDF), and combinations thereof.
26. The composite material according to claim 1, wherein the porosity of the layer is about 90% to about 95%.
27. A filter medium comprising the composite material of claim 1.
28. A liquid filter medium comprising the composite material of claim 1.
29. An oil filter comprising the composite material of claim 1.
30. A gas filter comprising the composite material of claim 1.
31. A fuel filter comprising the composite material of claim 1.
32. A hydraulic filter comprising the composite material of claim 1.
33. A chemical filter comprising the composite material of claim 1.
34. A filter medium, comprising: The first layer comprises wet-laid fibers and meltblown fibers; as well as The support structure in contact with the first layer.
35. The filter medium of claim 34, wherein the maximum pore size of the filter medium is less than about 30 micrometers.
36. The filter medium of claim 34, wherein the wet-laid fibers and the meltblown fibers are calendered, and the maximum pore size is less than about 13 micrometers.
37. The filter medium of claim 34, wherein the average flow pore size of the filter medium is less than about 15 micrometers.
38. The filter medium of claim 34, wherein the wet-laid fibers and the meltblown fibers are calendered, and the average flow pore size is less than about 7 micrometers.
39. The filter medium of claim 34, wherein the ratio of the maximum pore size to the average flow pore size of the filter medium is about 2.5 or less.
40. The filter medium according to claim 34, wherein the basis weight of the wet-laid fibers is at least about 50 gsm.
41. The filter medium of claim 40, wherein the basis weight is about 50 gsm to about 200 gsm.
42. The filter medium according to claim 40, wherein the basis weight of the meltblown fiber is from about 20 gsm to about 100 gsm.
43. The filter medium according to claim 34, wherein the wet-laid fiber is a foam-laid fiber.
44. The filter medium of claim 34, wherein the wet-laid fibers comprise materials selected from the group consisting of polypropylene, polyester, polypropylene, copolyamide, polyethylene, polycarbonate, polyacrylate, polyacrylonitrile, polystyrene, styrene-maleic anhydride, propylene, polyimide, polyetherketone, cellulose ester, nylon and polyamide, acrylics, vinyl acetate, ethylene-vinyl acetate, styrene-butadiene, ethylene / vinyl chloride, vinyl acetate copolymer, latex, epoxy resin, polyurethane, cellulose, styrene, and combinations thereof.
45. The filter medium of claim 34, wherein the wet-laid fibers comprise polyester.
46. The filter medium of claim 34, wherein the meltblown fiber comprises polyester.
47. The filter medium of claim 34, wherein the support structure comprises a mesh containing strands.
48. The filter medium of claim 47, wherein the basis weight of the strands is at least about 100 gsm.
49. The filter medium of claim 48, wherein the basis weight is at least about 110 gsm.
50. The filter medium of claim 34, wherein the support structure is ultrasonically bonded to the first layer at a plurality of attachment points.
51. The filter medium according to claim 47, wherein the mesh comprises a material selected from the group consisting of high-density polyethylene (HDPE), polyethylene, polypropylene (PP), metallocene PP, polylactic acid (PLA), thermoplastic polymers, nylon, polybutylene terephthalate (PBT), thermoplastic elastomer (TBE), polyphenylene sulfide (PPS), polyvinylidene fluoride (PVDF), and combinations thereof.
52. The filter medium according to claim 34, wherein the porosity of the first layer is about 90% to about 95%.
53. A liquid filter medium comprising the filter medium of claim 34.